The Influence of Influencer Marketing and Electronic Word of Mouth on Purchase Decisions Through Brand Trust as a Mediating Variable for Facetology Sunscreen Products in Pekanbaru - Rialdi, Rendi; Martias, Dony (Basecamp Economics PubMed, 2025)
This study aims to analyze the influence of influencer marketing and electronic word of mouth (E-WOM) on purchase decisions through brand trust as a mediating variable on Facetology Sunscreen products in Pekanbaru. This research used a quantitative method with purposive sampling, totaling 98 respondents aged 13-28 years who had purchased or used Facetology sunscreen products. Data analysis used SEM-PLS with SmartPLS 4.0 software. The results showed that influencer marketing and E-WOM positively and significantly influence brand trust and purchase decisions, both directly and indirectly. Brand trust mediates the influence of influencer marketing and E-WOM on purchase decisions.